"CONSCIOUS EFFECT ON MAINTAINING THE QUALITY IN THE FOOD PROCESSING INDUSTRY" - Omkar Vaity (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The food processing industry has in recent years gained importance as a sunrise industry for the accelerating economic development in India. Green marketing is a challenge handled by company in addition to environmental issues connected with manufacture and processing. Green commercialization is an organization's attempt to create, distribute, price and advocate end products which do not harm consumption, manufacturing resources and the environment. The main objective of this paper was to understand industrial youth behaviour with regard to diet and to understand the connection between workers' wage and dietary food by using a structured survey, as well as the data collected at different locations in the suburban area of Bhopal. 100 participants participated. These studies provide a helpful insight into foodstuffs by analysing the richness factor and food awareness.